System of Mythonyms in Poetry of Ivan Bunin - O. A. Selemeneva (Научный диалог)
The article is devoted to one of the problems of literary onomastics — an inventory of onomastic units of literary texts as an integral part of the vocabulary of the language of a particular writer. The relevance  of the chosen topic is due to the poorly studied issue of the mythonymicon of poetry and prose  by I. A. Bunin.   The novelty of the work is associated with the description of  the  mythological names  of Bunin the poet as  an  integral system.  The classification of  mythonyms  is  based  on five principles: the source  from  which  the name was used (there were three such sources: etiological, anthropogonic, heroic, cult and other  types of myths;  religious  and philosophical literature; multi-genre works of Slavic folklore); the nominated image of a fantastic object (eleven semantic groups are recorded: mythoanthroponyms, theonyms, demononyms, mythotonyms, mythohydronyms,   mythoornithonyms, etc.);  etymology  (otonymic, otapellative and special contextual mythological names are marked); structural type (simple or oneword  mythonyms,   complex,   represented by a bilexeme, and compound mythonyms, two-word and three-word ones are  fixed);  the presence of connotations in semantics (names with negative and positive connotative backgrounds were found).  The  author  comes to  the  conclusion  that  mythonyms  in I.A.Bunin's poetry become those stable linguistic signs that  carry  a  huge  amount  of historical and cultural information and  have a rich associative potential, accumulating the specifics of the writer's worldview, they contribute to the modeling of the text space.